Engine Back-up System in Flight Test Campaigns: a new Approach to the Height-Velocity Diagram Demonstration - Taheri, S.; Delavet, A. (My University, 2023)
The Height-Velocity (H/V) diagram is one of the key stages in the Maximum Take-Off Weight (MTOW) demonstration during the certification of a new helicopter or in the event of an increase in mass of an existing helicopter. The recent development of hybrid propulsion solutions allows for the implementation of an electric engine back-up system (EBS). In case of thermal engine failure, this electric power assistance could change the paradigm. Between July 2021 and May 2022, Airbus Helicopters carried out an extensive flight test campaign on the H130 Flightlab presented in this paper. The EBS installed in the Flightlab provides electrical assistance of about 100kW in case of engine failure. Preliminary studies had shown that it could allow a MTOW increase close to 200kg without an H/V diagram modification on the H130 helicopter type. To avoid flying above the certified MTOW on the Flightlab prototype, Airbus Helicopters used the H130 performance model to convert the 200kg target of mass increase to a H/V diagram area reduction, thus minimizing the applied stress constraint during that campaign. Moreover, battery autonomy and time of charge limited the training of the flight test crew and the gradual approach to these critical points. Airbus Helicopters adapted the thermal engine software to simulate the EBS assistance. The analysis of the flight test results has demonstrated the validity of the mass to the H/V diagram reduction equivalence, successfully mitigating the risk in approach during the flight test procedure. Thanks to this process, Airbus Helicopters is now actively taking into consideration an H130 MTOW extension with a hybrid propulsion system for an upcoming certification, the first of its kind in the helicopter industry.
Keywords: Test & Evaluation